2016
DOI: 10.1039/c6ra24184k
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behaviour of Pu4+and PuO22+on amido amine-functionalized carbon nanotubes: experimental and computational study

Abstract: Amido amine-functionalized multi-walled carbon nanotubes (MWCNT-AA) were used for efficient and selective solid phase separation of plutonium(iv) and plutonium(vi).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For the isotherm analysis, the Langmuir, D–R and Freundlich models were considered. These are summarized below: 13 where C e (mg L −1 ) is the equilibrium concentration; q e is the amount of metal ion adsorbed (mg g −1 ) on the sorbent at equilibrium; q 0 is the sorption capacity; b is the sorption energy; X m and β are the maximum sorption capacity and activity coefficient, respectively; K f (mg g −1 ) is the Freundlich isotherm constant; and n is the sorption intensity. The experimental data were fitted into the linear equations of these isotherms mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…For the isotherm analysis, the Langmuir, D–R and Freundlich models were considered. These are summarized below: 13 where C e (mg L −1 ) is the equilibrium concentration; q e is the amount of metal ion adsorbed (mg g −1 ) on the sorbent at equilibrium; q 0 is the sorption capacity; b is the sorption energy; X m and β are the maximum sorption capacity and activity coefficient, respectively; K f (mg g −1 ) is the Freundlich isotherm constant; and n is the sorption intensity. The experimental data were fitted into the linear equations of these isotherms mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Obtained kinetics data were fitted into three different kinetics models: Lagergren first order ( SE1 ), pseudo-second order ( SE2 ), and intraparticle diffusion ( SE3 ) (Figures S1–S3). Regression coefficient analysis showed that sorption kinetics fits best in the pseudo-second order model. The sorption isotherm shown in Figure C describes the maximum sorption capacity for UO 2 2+ ≈ 193 mg g –1 and Th 4+ ≈ 227 mg g –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the sorption process in more detail, the kinetic data was fitted to various sorption models, such as Lagergren (pseudo-first-order), intraparticle diffusion, and pseudo-second-order kinetics models. The Lagergren’s first-order kinetics is represented by the following equation ,, log ( q normale q t ) = loq 0.25em q e kt 2.303 where q e and q t are the amounts of radionuclides adsorbed by the PS-DGA-CNT beads at equilibrium and at time t , respectively; k is the adsorption rate constant and t is the time in minutes. The linear regression coefficients for the Lagergren first-order kinetic model for Am 3+ and Eu 3+ were found to be 0.9668 and 0.9465, respectively.…”
Section: Resultsmentioning
confidence: 99%